Australian office procedures - Hopkins, Linda; Hamilton, Barbara (Milton, Qld. : Jacaranda Press, 1990)
This book is about: The office environment; Introduction to the computerised office; Telecommunications and office automation; Business references; ...
Keywords: Australia; Office procedures; Office procedures -- Australia